Applicability of altman's z-score model in predicting financial distress towards PN17 companies in Malaysia / Fairus Farizah Razali - Razali, Fairus Farizah (Faculty of Business Management, 2017)
PN 17 is known as Practice Note 1. It is for listed company that having a financial distress and issued by Malaysian Stock Exchange. The company will had a financial distress when the business failed to meet the requirement of the minimum capital and equity. Which is the company had less than 25% from the paid up capital. By using financial ratio analysis method can detect the failure that happen to this companies. In 2016 under PN17 list there are 17 companies that listed on Malaysian Stock Exchange classified. According with their existing standard the company will entered into PN17. However there are investors doesn’t even know about the status form these listed company. So, a real and attention for these companies has not been given also scientific researchers and analytical studies are still lacking for companies that listed in PN17. The aims for this research is to measure the financial performance by using financial profitability ratios (Working Capital to Total Assets, Return on Total Assets, Retained Earnings to Total Assets, Market Value of Equity to Total Liabilities and Asset turnover) in determining the financial disaster of companies. The available data collected from the DataStream covering the period from 2011 to 2013 were used in the analysis. Furthermore, by using Altman’s Z-Score can be used to testing the performance of the company whether become failure or non failure company.